Influence of social media followers on revenues: a pilot study of Europe’s top 20 football clubs - Pérez-González, Benito; Valcarce-Torrente, Manel; Guevara-Pérez, Juan Carlos; López-Carril, Samuel (Academia Revista Latinoamericana de Administracion, 2025)
Purpose In an increasingly digitised sport ecosystem, social media has emerged as a primary tool for sport managers to engage with industry stakeholders. This pilot study aims to investigate whether there is a correlation between the number of followers on football teams' social media accounts and the annual revenue they generate. Design/methodology/approach We sampled the number of followers on Facebook, Twitter, Instagram and TikTok of the top 20 European football clubs based on their annual revenue. Employing a balanced panel data approach for the four years (2020–2023), our analysis comprises a total of 80 observations in a regression model. Findings The study’s findings indicate a correlation between the number of social media followers and annual revenue, with particularly strong correlations observed for Facebook and TikTok. Additionally, significant growth in the number of followers on Instagram and TikTok was identified during the study period. Research limitations/implications The study’s limitations suggest opportunities for future research. Exploring the bidirectional SP–FP relationship could reveal how financial sustainability impacts fans’ social media behaviour. Further studies might analyse specific leagues, other sports or platforms like YouTube and WhatsApp or apply longitudinal data to a single platform. Additionally, qualitative or mixed methods, such as interviews or focus groups with stakeholders, could enrich understanding of social media’s subjective aspects. This pilot study does not claim definitive conclusions but aims to inspire further research in the dynamic realm of social media and digital technologies, broadening knowledge in this rapidly evolving field. Originality/value The findings have implications for sport managers in designing and optimising social media management strategies, given their potential impact on revenue generation. The study contributes to a better understanding of the revenue-generating potential of social media in the football industry. Furthermore, this is one of the first studies to simultaneously analyse the use of Facebook, Twitter, Instagram and TikTok by football clubs over four years.
Objetivo En un ecosistema deportivo cada vez más digitalizado, los medios sociales han emergido como una herramienta clave para que los gestores deportivos interactúen con los diferentes grupos de interés de la industria. Este estudio piloto tiene como objetivo investigar si existe una correlación entre el número de seguidores en las cuentas de medios sociales de los equipos de fútbol y los ingresos anuales que estos generan. Diseño/metodología/enfoque Se analizó el número de seguidores en Facebook, Twitter, Instagram y TikTok de los 20 principales clubes de fútbol europeos según sus ingresos anuales. Empleando un enfoque de datos de panel balanceado para el periodo de cuatro años (2020–2023), nuestro análisis incluye un total de 80 observaciones en un modelo de regresión. Resultados Los hallazgos del estudio indican una correlación entre el número de seguidores en los medios sociales y los ingresos anuales, con correlaciones especialmente fuertes observadas en Facebook y TikTok. Además, se identificó un crecimiento significativo en el número de seguidores en Instagram y TikTok durante el periodo de estudio. Originalidad/valor Los resultados tienen implicaciones para los gestores deportivos en el diseño y optimización de estrategias de gestión de los medios sociales, dada su influencia potencial en la generación de ingresos. El estudio contribuye a una mejor comprensión del potencial de generación de ingresos de los medios sociales en la industria del fútbol. Además, es uno de los primeros estudios que analiza simultáneamente el uso de Facebook, Twitter, Instagram y TikTok por parte de los clubes de fútbol a lo largo de cuatro años.
Keywords: football clubs; social media; revenues; followers; fan engagement; stakeholder theory; sport management; facebook; twitter; instagram; TitkTok; clubes de fútbol; medios sociales; ingresos; seguidores; interacción con los aficionados; teoría de las partes interesadas; gestión deportiva; digitalización; Scopus; JCR